Barriers and facilitators to changes in adolescent physical activity during COVID-19 - Kwok Ng; Jemima Cooper; Fiona McHale; Joanna Clifford; Catherine Woods (BMJ Open Sport & Exercise Medicine)
Objectives COVID-19 restrictions reduced adolescents’ opportunities for physical activity (PA). The purpose of this study was to examine how adolescent PA changed during school closures, to identify the key barriers and facilitators for these changes during lockdown and to use this information to understand how to manage future crises’ situations positively to prevent physical inactivity.Methods Irish adolescents (N=1214; ages 12–18 years) participated in an online cross-sectional study during April 2020, including items on PA level, changes in PA and reasons for change in an open-ended format. Numeric analyses were through multiple binary logistic regressions, stratified by changes in PA during lockdown and inductive analysis of open coding of text responses.Results Adolescents reported they did less PA (50%), no change (30%) or did more PA during lockdown (20%). Adolescents who did less PA were more likely to be overweight (OR=1.8, CI=1.2–2.7) or obese (OR=2.2, CI=1.2–4.0) and less likely to have strong prior PA habits (OR=0.4, CI=0.2–0.6). The most cited barriers to PA were coronavirus, club training cancelled and time. Strong associations for doing more PA included participation in strengthening exercises at least three times in the past 7 days (OR=1.7, CI=1.3–2.4); facilitators were more time, coronavirus and no school.Conclusion COVID-19 restrictions were both a barrier to and an opportunity for PA. Parents, schools, public health, communities and industries must collaborate to prevent physical inactivity at times of crisis, especially for vulnerable groups.